ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИ УЧУН “ДАРС ЖАДВАЛИ” АХБОРОТ ТИЗИМИНИ ИШЛАБ ЧИҚИШ - Зиядуллаев, Д.Ш.; Сапаров, А.Д.; Рахмонов, М.Ш.; Абдувохидов, М. (SCIENCE and SOCIETY, 2018)
The article is devoted to the presentation of the methods of computer-aided scheduling of the university’s lessons, the main directions of development, the available results on the creation of the schedule in the semi-automatic mode.